1993
DOI: 10.1093/nar/21.15.3507
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a DNA binding domain in the C-terminus of HIV-1 integrase by deletion mutagenesis

Abstract: The integrase (IN) protein of human immunodeficiency virus type 1 (HIV-1) catalyzes site-specific cleavage of 2 bases from the viral long terminal repeat (LTR) sequence yet it binds DNA with little DNA sequence specificity. We have previously demonstrated that the C-terminal half of IN (amino acids 154-288) possesses a DNA binding domain. In order to further characterize this region, a series of clones expressing truncated forms of IN as N-terminal fusion proteins in E.coli were constructed and analyzed by Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 35 publications
2
98
0
Order By: Relevance
“…In our UV cross-linking assays with oligonucleotides, the GP(Y/F) fragment did bind DNA with high efficiently. The finding that a region of the C-terminal domain bound DNA and that it was a nonspecific DNA binding activity paralleled the activities of other INs (31)(32)(33)(34)(35)(36). However, our study of single amino acid substitutions indicated that the GP(Y/F) residues within the GP(Y/F) fragment did not contribute to this DNA binding.…”
Section: Discussionsupporting
confidence: 56%
“…In our UV cross-linking assays with oligonucleotides, the GP(Y/F) fragment did bind DNA with high efficiently. The finding that a region of the C-terminal domain bound DNA and that it was a nonspecific DNA binding activity paralleled the activities of other INs (31)(32)(33)(34)(35)(36). However, our study of single amino acid substitutions indicated that the GP(Y/F) residues within the GP(Y/F) fragment did not contribute to this DNA binding.…”
Section: Discussionsupporting
confidence: 56%
“…In line with this observation, it is worth noting that the C-terminal domain of IN, which has been implicated in both nonspecific (Engelman et al, 1994;Heuer and Brown, 1997;Lutzke et al, 1994;Vink et al, 1993;Woerner and Marcus-Sekura, 1993) and specific (Gao et al, 2001) DNA binding, is intact in the K156E/K159E mutant. Consistent with this notion, a considerable degree of nuclear accumulation was evident in transiently transfected cells at steady-state (Fig.…”
Section: Localization Of In Fused To An Nesmentioning
confidence: 61%
“…et al, unpublished) or by DNase I digestion followed by extraction under hypotonic conditions . These results highlight that HIV-1 IN tightly binds chromosomal DNA in vivo, a phenomenon that might be mediated by the nonspecific DNAbinding properties of the central core (Engelman et al, 1994;Heuer and Brown, 1997;Katzman and Sudol, 1995;Shibagaki and Chow, 1997) and/or C-terminal domains (Engelman et al, 1994;Heuer and Brown, 1997;Lutzke et al, 1994;Vink et al, 1993;Woerner and Marcus-Sekura, 1993).…”
Section: Resultsmentioning
confidence: 91%
“…The modest integration defect exhibited by the RRR mutant may be attributable to a lack of acetylation, but we believe that the lysine-to-arginine changes may degrade one of the functional activities of the integrase, perhaps by altering the ability of the IN CTD to bind either viral or target DNA (3,4,7,8,10,11,20,21,27,40,41). Although attempts to characterize integrase-DNA binding by computer modeling have been made (1,5,6,17,22,37,44), definitive structural details await description.…”
mentioning
confidence: 99%
“…Recently it has been shown that HIV-1 integrase (IN) is a substrate for histone acetyltransferase (HAT)-mediated p300 posttranslational acetylation both in vitro and in vivo (3). Interestingly, p300 modification targets lysine residues within the IN C-terminal domain (CTD), a domain known to possess intrinsic DNA binding activity in vitro (10,11,20,21,27,40,41). Since p300 acetylation affects the ability of a variety of DNA binding proteins to interact specifically with their respective target DNAs (12-14, 19, 30, 35, 42), these observations are of significant interest, especially in light of the related finding that posttranslational acetylation by p300 regulates HIV-1 integration (3).…”
mentioning
confidence: 99%